PENGARUH PEOPLE DAN PHYSICAL EVIDENCE TERHADAP MINAT KUNJUNGAN DI RUMAH MAKAN KHAS BETAWI BABEH SADELI, PONDOK AREN, TANGERANG - Desafitri, Linda; Irfal, Irfal; Haryono, Joko (JURNAL EKOBIS DEWANTARA, 2024)
This research aims to determine the influence of people and physical evidence on interest in visiting Betawi Babeh Sadeli Restaurant, Pondok Aren, South Tangerang, Banten Province. This type of research is descriptive quantitative with multiple analysis methods. The data collection technique was carried out by distributing questionnaires to respondents, using a Likert scale. The sampling technique used was accidental sampling. The population in the research were all consumers who visited the Babeh Sadeli Betawi Restaurant, Pondok Aren. The sample consisted of 100 respondents. The results of partial research on people and physical evidence influence interest in visiting. Research shows that service and the physical environment influence the customer experience at a restaurant. A friendly and professional attitude increases visitor satisfaction and influences their interest in returning. An attractive interior and cleanliness are also important in providing a positive first impression to customers. The combination of the two creates an overall positive experience, encouraging customers to return and recommend the restaurant to others. Restaurant practitioners are advised to provide employee training for friendly, professional and knowledgeable service. Then also interior design, cleanliness and food presentation to create a positive impression.